2021
DOI: 10.1016/j.artd.2020.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Altmetric Score and Traditional Bibliometrics in Total Joint Arthroplasty Research

Abstract: Background Citation analysis is commonly used to evaluate the impact of academic publications within an area of study. The purpose of this study is to review the publications with the highest Altmetric scores related to total hip arthroplasty (THA) and total knee arthroplasty (TKA) and assess the correlation with traditional bibliometrics. Methods Altmetric scores were obtained for the top articles relating to THA and TKA and organized from highest to lowest scores. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…This may stem from the reader’s tendency to share articles from the journals with a higher impact factor. Although a similar trend was found in total knee literature, a correlation between AAS and impact factor was not found in sports science and total hip arthroplasty literature [ 71 , 72 , 74 ]. High-impact journals may be more active in engaging with social media, or the quality of studies may play a role in this association.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This may stem from the reader’s tendency to share articles from the journals with a higher impact factor. Although a similar trend was found in total knee literature, a correlation between AAS and impact factor was not found in sports science and total hip arthroplasty literature [ 71 , 72 , 74 ]. High-impact journals may be more active in engaging with social media, or the quality of studies may play a role in this association.…”
Section: Discussionsupporting
confidence: 60%
“…At the same time, the mean AAS was 63.4 ± 164.8, and the median AAS was 10.5. Previous studies in other orthopedic specialties have found a median AAS of 4 to 235, depending on the topic and age of the publication [ 66 , [68] , [69] , [70] , [71] ]. In line with other authors, we found a significant but weak correlation between the citation number and AAS across the included papers [ [3] , [67] , [68] , [69] , [72] , [73] ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between AAS and citation rate have previously been described in orthopaedic literature. 4,[7][8][9][10] AAS has thus gained utility and popularity for evaluating the level of public interest in the current digital era. Contrary to these findings, Collins et al 32 found no correlation between AAS and citations across 15 orthopaedic journals.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, recent advances in digital media have prompted the development of alternative metrics, such as the Altmetric Attention Score (AAS), which measures the real-time impact of studies on digital news and social media platforms. Although AAS and citation rates have consistently been shown to correlate with each other, 4,[7][8][9][10] there is conflicting evidence to suggest an association between these metrics and external factors such as study quality and results. 7,11,12 Furthermore, it is unclear whether there are characteristics distinguishing high-quality orthopaedic studies published in orthopaedic-specific journals and medical journals, which historically have larger audiences.…”
mentioning
confidence: 99%
“…Altmetrics have also been used as an adjunct for evaluating the impact of published studies, pointing to both a correlation with citation frequency and an association with social media exposure [19,27,30]. The Altmetric Attention Score (AAS) is one of the most widely used tools used to quantify a publication's online footprint.…”
Section: Introductionmentioning
confidence: 99%